Sitagliptin Increases Beta-Cell Function and Decreases Insulin Resistance in Newly Diagnosed Vietnamese Patients with Type 2 Diabetes Mellitus - Le TD (Dove Medical Press, 2020)
Tuan Dinh Le,1,* Nga Thi Phi Nguyen,2,3,* Son Tien Nguyen,2,3 Hoa Thi Thanh Tran,4 Lan Thi Ho Nguyen,4 Hoang Huy Duong ,1 Ha Manh Nguyen ,4 Binh Nhu Do5,* 1Department of Internal Medicine, Thai Binh University of Medicine and Pharmacy, Thai Binh, Vietnam; 2Department of Endocrinology, Military Hospital 103, Ha Noi, Vietnam; 3Department of Rheumatology and Endocrinology, Vietnam Military Medical University, Ha Noi, Vietnam; 4The National Endocrinology Hospital, Ha Noi, Vietnam; 5Division of Military Science, Military Hospital 103, Ha Noi, Vietnam*These authors contributed equally to this workCorrespondence: Nga Thi Phi Nguyen; Binh Nhu Do Email ngabv103@yahoo.com.vn; nhubinh.do@vmmu.edu.vnIntroduction: To investigate effects of Sitagliptin on the enhancement of beta-cell function, reducing insulin resistance, serum glucagon like peptide-1 (GLP-1) concentrations and blood glucose in patients with type 2 diabetes mellitus (T2D) and suggest one of the underlying mechanisms on beta-cell function and insulin resistance.Patients and Methods: This was a cross-sectional and observational study in comparison to the control group. A study population of 44 newly diagnosed patients with T2D treated with Sitagliptin with a dose of 100 mg/day for 3 months was analyzed to compare 52 healthy participants. Indices for beta-cell function, peripheral insulin sensitivity, and insulin resistance were calculated with homeostasis model assessment 2 (HOMA2) calculator and compared. Serum GLP-1 concentrations were analyzed, and regression analysis was conducted to find the correlations between GLP-1 and beta-cell function and insulin resistance.Results: Newly diagnosed patients with T2D witnessed a significant reduction in beta-cell function, serum GLP-1 concentrations at the time of diagnosis. After treatment with Sitagliptin 100 mg/day, they achieved significant improvements in beta-cell function, peripheral insulin sensitivity and insulin resistance. Serum GLP-1 concentrations were increased significantly to those levels in the control group and correlated with peripheral insulin sensitivity and insulin resistance in patients whose beta-cell functions improved.Conclusion: Sitagliptin improved beta-cell function, insulin resistance and blood glucose in newly diagnosed patients with T2D. Meanwhile, Sitagliptin ameliorated serum GLP-1 concentrations, which contributed to the enhancement of beta-cell.Keywords: Sitagliptin, serum GLP-1 concentrations, beta-cell function, insulin resistance, newly diagnosed patients with type 2 diabetes mellitus